Physical and chemical changes in juvenile and mature wood of shizolobium parahyba caused by thermal modification - Calonego, F. W. [UNESP]; Severo, E. T.D. [UNESP]; Sansígolo, C. A. [UNESP]; De Brito, A. F. [UNESP] (Forest Research Institute Malaysia, 2020)
In the Brazilian Atlantic Forest, the pioneer species Schizolobium parahyba, known as guapuruvu, is a fastgrowing tree with potential for ecological restoration in forest management projects. However, an undesirable feature of this wood is the pronounced presence of juvenile wood leading to poor dimensional stability. This study evaluates the effect of various thermal modification intensities on the physicochemical properties of S. parahyba juvenile and mature wood. Boards sawn from 15-year-old trees were thermally modified at three different temperatures (180, 200 and 220 °C). Thermal modification decreased the density (up to 9%), moisture content (up to 9.1%) and volumetric swelling (up to 54.1%). For chemical properties, when the wood was submitted to thermal modification at 220 °C, significant increase was detected in the respective extractive (up to 286.5%) and lignin content (up to 41.7%), and reduction in the holoceluloses (up to 25.0%). It was demonstrated that basic density was not the most suitable parameter for evaluating the quality of thermally modified wood. The influence of thermal modification was equal in juvenile and mature wood.
Keywords: Density of wood; Dimensional stability; Guapuruvu; Holocelluloses content; Thermally modified wood